Study of machine learning techniques for disease detection in the eye - Yogaindran S/O Murugan (Nanyang Technological University, 2023)
Machine learning is a branch of artificial intelligence in which a computer learns to make predictions from a set of data without explicit human intervention. In recent years, deep learning emerges as one of the most promising machine learning methods due to its powerful generalizing capability to different modality of data. For medical Summary diagnosis, machine learning-based systems have been deployed in several subfields such as oncology, cardiology and ophthalmology to help doctors identify diseased areas from medical images within short period of time. This project will investigate segmentation techniques for OCT angiography and multimodal learning for comprehensive retinal diseases detection and diagnosis.